Allergy-Related Diseases and Risk of Breast Cancer: The Role of Skewed Immune System on This Association. (July 2019) - Sadeghi, Fatemeh; Shirkhoda, Mohammad
Background: The role of allergy in breast cancer (BC) development remains inconclusive. A comprehensive review article is required to present and discuss all findings on this topic and to clarify the association between allergic disorders and the risk of BC. Objective: We aimed to explain the association between atopy, different types of allergic disorders, and the risk of BC. Moreover, we explored the immunological mechanism behind this association. Methods: We electronically reviewed publications in PubMed from 1979 to 2018 relating to atopy, allergy, asthma, atopic dermatitis, allergic rhinitis, food allergy, drug allergy, immunoglobulin E (IgE) or prick test, and BC. Results: Most of the identified studies demonstrated nonsignificant results. However, the pattern of the results indicated an increased risk of BC in individuals with a history of allergies. The majority of studies reported higher prevalence of atopic dermatitis and allergic rhinitis among individuals with BC compared to the control groups. Similarity, most of the studies revealed an increased risk of BC among people with a positive history of atopic using IgE specific or prick test. However, a null association was reported in most of the asthmatic studies, and controversial results were detected in the individuals with history of food and drug allergies. Conclusion: The majority of findings were not statistically significant. Moreover, bias and other methodological problems are the major issues, which make it challenging to compare the findings of different studies and reach a strong conclusive result. However, the pattern of the results from most studies indicated that allergic diseases might be associated with an increased risk of BC. Skewed immune system toward T-helper 2 might have an important role in this association.